Legal guarantees for the protection of the rights to life and to health care of the child extracted alive as a result of abortion (Stato, Chiese e pluralismo confessionale, 2015)
The article has been subjected to peer review, and has been prepared in connection with the appeal of the Representation of the Russian Orthodox Church in StrasbourgSUMMARY: 1. Problem description - 2. State of Russian Legislation regulating of the legal status of the child extracted alive as a result of abortion - 3. Legal basis for the recognition of human dignity and the right to life of the child extracted alive as a result of abortion - 4. Legal guarantees of recognition of the right to life and human dignity of the child extracted alive as a result of abortion and emergency medical care in foreign legislation - 5. Conclusions.